Effect of Repeat Vaccination on Immunogenicity of Quadrivalent Cell-Culture and Recombinant Influenza Vaccines Among Healthcare Personnel Aged 18–64 Years: A Randomized, Open-Label Trial. (29th August 2022) - Gaglani, Manjusha; Kim, Sara S; Naleway, Allison L; Levine, Min Z; Edwards, Laura; Murthy, Kempapura; Dunnigan, Kayan; Zunie, Tnelda; Groom, Holly; Ball, Sarah; Jeddy, Zuha; Hunt, Danielle; et al.
Abstract: Background: Antibody responses to non–egg-based standard-dose cell-culture influenza vaccine (containing 15 µg hemagglutinin [HA]/component) and recombinant vaccine (containing 45 µg HA/component) during consecutive seasons have not been studied in the United States. Methods: In a randomized trial of immunogenicity of quadrivalent influenza vaccines among healthcare personnel (HCP) aged 18–64 years over 2 consecutive seasons, HCP who received recombinant-HA influenza vaccine (RIV) or cell culture–based inactivated influenza vaccine (ccIIV) during the first season (year 1) were re-randomized the second season of 2019–2020 (year 2 [Y2]) to receive ccIIV or RIV, resulting in 4 ccIIV/RIV combinations. In Y2, hemagglutination inhibition antibody titers against reference cell–grown vaccine viruses were compared in each ccIIV/RIV group with titers among HCP randomized both seasons to receive egg-based, standard-dose inactivated influenza vaccine (IIV) using geometric mean titer (GMT) ratios of Y2 post-vaccination titers. Results: Y2 data from 414 HCP were analyzed per protocol. Compared with 60 IIV/IIV recipients, 74 RIV/RIV and 106 ccIIV/RIV recipients showed significantly elevated GMT ratios (Bonferroni corrected P < .007) against all components except A(H3N2). Post-vaccination GMT ratios for ccIIV/ccIIV and RIV/ccIIV were not significantly elevated compared with IIV/IIV except for RIV/ccIIV against A(H1N1)pdm09. Conclusions: In adult HCP, receipt of RIV in 2 consecutive seasons or the second season was more immunogenic than consecutive egg-based IIV for 3 of the 4 components of quadrivalent vaccine. Immunogenicity of ccIIV/ccIIV was similar to that of IIV/IIV. Differences in HA antigen content may play a role in immunogenicity of influenza vaccination in consecutive seasons. Clinical Trials Registration: NCT03722589. Abstract : Healthcare personnel aged 18–64 years who received 2 consecutive seasons of quadrivalent recombinant-hemagglutinin influenza vaccine showed higher post-vaccination hemagglutination-inhibition antibodies against 3 components compared with those who received egg-based inactivated vaccine; those who received the cell-culture vaccines did not.